2018
DOI: 10.1016/j.robot.2018.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Designing a socially integrated mobile robot for ethological research

Abstract: A robot introduced into an animal group, accepted by the animals as conspecifics, and capable of interacting with them is a very efficient tool for ethological research, particularly in studies of collective and social behavior. In this paper, we present the implementation of an autonomous mobile robot developed by the authors to study group behavior of chicks of the domestic chicken (Gallus gallus domesticus). We discuss the design of the robot and of the experimental setup that we built to run animal-robot e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 62 publications
0
13
0
Order By: Relevance
“…The Distance between larvae and adult individuals is used as a measure of social interaction in Drosophila 64-70 as well as in other species [71][72][73][74][75] . An effect of strain and sex has been previously found on Distance in the DGRP lines 64 .…”
Section: Position the Distributions Of Positions (Seementioning
confidence: 99%
“…The Distance between larvae and adult individuals is used as a measure of social interaction in Drosophila 64-70 as well as in other species [71][72][73][74][75] . An effect of strain and sex has been previously found on Distance in the DGRP lines 64 .…”
Section: Position the Distributions Of Positions (Seementioning
confidence: 99%
“…By means of this interaction system, we found that gregarious locusts displayed a higher performance of endurance jumping locomotion than that of solitary ones. Recently, a robotic cockroach (Halloy et al ., ) or chicken (Gribovskiy et al ., ) had been employed to explore the population behavior of shelter selection or imprinting, respectively. Because gregarious locusts have a typical collective behavior (Yates et al ., ; Ariel & Ayali, ), we supposed that a group of endurance jumping robots would be very useful for understanding the interaction with locust individuals and swarm formation.…”
Section: Discussionmentioning
confidence: 99%
“…The Distance between larvae and adult individuals is used as a measure of social interaction in Drosophila 62-68 as well as in ! 6 other species [69][70][71][72][73] . An effect of strain and sex has been previously found on Distance in the DGRP lines 62 .…”
Section: Positionmentioning
confidence: 99%